Pneumonia as a Life-Threatening Disease among Under-Five Children: A Descriptive Phenomenology Study - Restuning Widiasih; Binahayati Rusyidi; Nenden Nur Asriyani Maryam; Tata Sudrajat (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Pneumonia is the largest infectious disease in under-five children worldwide, including Indonesia. Comprehensive and integrated approaches are essential to prevent and control childhood pneumonia by involving the community, such as health cadres. Health cadres are the main support for the children's health that liaison between the community and health workers; however, limited exploration of cadres' perspectives about children’ health. . This study aimed to explore the perceptions and experiences of health cadres regarding childhood Pneumonia. This descriptive phenomenological approach used semi-structured interviews with 29 cadres in two different districts. Data collection was used in-depth interviews with a semi-structured approach. The data were analyzed using a comparative analysis approach in qualitative research. The study found three main themes; Pneumonia is a life-threatening disease, the characteristic of Pneumonia, and the need for assistance in preventing and controlling Pneumonia. Various perceptions of Pneumonia may affect the cadres' actions in the children’s health.This study informed  health workers for developing  an innovative training and programs, which will maximize the cadres' roles and capabilities in Pneumonia.